BUILDING 21st-CENTURY SKILLS WITH STEAM-PjBL - Suryaningsih, Siti; Agung, Salamah; Barke, Hans-Dieter; Nisa, Fakhira Ainun (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2024)
During the 21st century, students are encouraged to develop skills that enable them to deal with real-life problems. The purpose of this study is to analyze what kind of 21st-century skills can be built during a teaching and learning process in the classroom. Science, Technology, Engineering, Arts, and Mathematics (STEAM) approach through a project-based learning (PjBL), or STEAM-PjBL-based learning, seems to provide a promise in the development of 21st-century skills of students. This study, therefore, is conducted to reveal the kind of skills that can be built during the STEAM-PjBL learning process. Using a literature review, this study collects and analyzes relevant articles from national and international journals through several search engine systems, such as Taylor & Francis Online, Springer, etc., and indexed databases, such as SCOPUS, DOAC, and Eric, both from the period of 2014-2022. This study found that the 4Cs of the 21st-century skills, namely, critical thinking and problem solving, communication, collaboration, and creative thinking, can be built from the activities in each stage of the STEAM-PjBL learning process. While the skills are evident from the literature review, a further empirical study is encouraged to be conducted to ensure how the skills can be successfully developed and further improved